Acoustic noise levels and field distribution in 7 T MRI scanners - Shtrepi, Louena; Poggetto, Vinicius F. Dal; Durochat, Clement; Dubois, Marc; Bendahan, David; Nistri, Fabio; Miniaci, Marco; Pugno, Nicola Maria; Bosia, Federico (Frontiers in Physics, 2023)
Acoustic noise production during Magnetic Resonance Imaging is an important source of patient discomfort and leads to verbal communication problems, difficulties in sedation, and hearing impairment. To address these issues, in this paper we present a systematic characterization of the acoustic field distribution in a MRI cavity in a last generation 7 T scanner, in different spatial locations, with and without a phantom head. Analysis and comparison of various MRI sequences like Echo-planar imaging”, “Gradient echo”, “Spin echo” are carried out. Sound pressure levels are measured using standard statistical descriptors (Leq,Lmean, L90, and Lmode) using two prepolarized free-field microphones measuring pressure levels generated inside scanner cavities in a 50 Hz to 10 kHz range. Acoustic eigenmodes of the cavity are derived numerically in finite element simulations and compared to measurements. Equivalent sound pressure levels exceed 85 dB in the range between 500 and 3,000 Hz, and peak levels are consistently above 100 dB, i.e., the noise levels of 7 T scanners are higher than 3T and 1.5 T counterparts. The presence of the phantom head in the MRI scanner leads to increased noise levels (by 5–10 dB) in its vicinity, as a result of reflections occurring between the head and the bore reflective walls. Numerical finite element simulations allow to extrapolate the noise distribution in the entire cavity and to interpret experimental results and indicate that the frequencies at which the highest noise levels occur correspond to azimuthal or radial resonant modes of the MRI cavity, i.e., with a radially and azimuthally varying pressure field. These results can be useful for the design of future acoustic noise mitigation solutions.